2016
DOI: 10.1186/s12886-016-0319-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for choroidal detachment following rhegmatogenous retinal detachment in a chinese population

Abstract: BackgroudChoroidal detachment (CD) following primary rhegmatogenous retinal detachment (RRD) is a special type of RRD. The purpose of this study is to investigate the potential risk factors of RRD with CD in a Chinese population.MethodsAll of 201 consecutive RRD with CD patients and 210 RRD without CD patients were enrolled in this case–control retrospective study. The clinical data from these cases were reviewed here. Patients were undergone scleral buckling or encircling or both, or pars plana vitrectomy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 11 publications
5
61
1
Order By: Relevance
“…There were 26 (73.4%) patients with a history of IOP > 30 mmHg in two consecutive follow-ups in RRD-CD group, similar with those in RRD group (23, 43.4%, p = 0.23), but more than those in TRD group (10,22.2%, p < 0.001).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…There were 26 (73.4%) patients with a history of IOP > 30 mmHg in two consecutive follow-ups in RRD-CD group, similar with those in RRD group (23, 43.4%, p = 0.23), but more than those in TRD group (10,22.2%, p < 0.001).…”
supporting
confidence: 56%
“…There are several factors in RRD-CD which may in uence the changes of IOP. It is noted that RRD-CD patients tend to have low IOP [10] . What's more, the presence of PM or postoperative glaucoma are factors known to be able to cause signi cant IOP variations before and after PPV surgery.…”
Section: Factors That May Be Related To the Variation Of Al Measured mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, oedema of the ciliary body further reduces the generation of aqueous humour and causes prominent hypotony, deteriorating the dilatation and hyperpermeability of choroidal vessels and leading to progression of choroidal detachment. Therefore, a positive feedback loop is established [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of combined retinal detachment with associated choroidal detachment is reported about 2-8.6% [10][11][12]. Li et al [9].revealed that proportion of RRD/CD can be as high as 18.7% among RRD patients when diagnosed by UBM.…”
Section: Discussionmentioning
confidence: 99%